Pengaruh Kitosan Terhadap Kadar Residu Pb Ginjal Tikus Putih (Rattus Sp.) Jantan Yang Dipapari Plumbum Asetat - Ulina Catarina Jeni Simatupang (Universitas Negeri Medan, 2016)
The study aimed to determine the effect of chitosan on the kidney of rats (Rattus sp.) exposed to lead acetate. Thirty five male animals weighing 250g were divided into 7 groups: K group as a control (without treatment), P1 received Pb (40 mg/kg bw as lead acetate), while P2, P3, and P4, all received Pb (40 mg/kg bw) and chitosan (0,5%, 0,75%, and 1% respectively). P5 group received only chitosan (1%) and P6 group received acetic acid. After 7 weeks of treatment, the animals were sacrificed and the kidneys were isolated. Kidney damage was observed with residue of Pb in kidney tissue was evaluated using Atomic Absorption Spectrophotography. Chitosan able to decrease kidney damage resulted from Pb treatment. Residue of Pb in the kidney of rat exposed to Pb acetate was decreased after chitosan treatment. In conclusion, chitosan has the ability to reduce residue of Pb after exposed Pb. The effectiveness of chitosan as a chelating agent for Pb in the organs is important for further investigated. Keywords: Pb, chitosan, kidny, residual Pb,AAS